Cannabinoid Receptor 2 Signalling Bias Elicited by 2,4,6-Trisubstituted 1,3,5-Triazines - Oyagawa, Caitlin R. M.; de la Harpe, Sara M.; Saroz, Yurii; Glass, Michelle; Vernall, Andrea J.; Grimsey, Natasha Lillia (Frontiers in Pharmacology, 2018)
Cannabinoid Receptor 2 (CB2) is predominantly distributed in immune tissues and cells and is a promising therapeutic target for modulating inflammation. In this study we designed and synthesised a series of 2,4,6-trisubstituted 1,3,5-triazines with piperazinyl-alkyl or 1,2-diethoxyethane (PEG2) chains as CB2 agonists, all of which were predicted to be considerably more polar than typical cannabinoid ligands. In this series, we found that triazines containing an adamantanyl group were conducive to CB2 binding whereas those with a cyclopentyl group were not. Although the covalent attachment of a PEG2 linker to the adamantyl triazines resulted in a decrease in binding affinity, some of the ligands produced very interesting hCB2 signalling profiles. Six compounds with notable hCB2 orthosteric binding were functionally characterised in three pathways; internalisation, cyclic adenosine monophosphate (cAMP) and ERK phosphorylation (pERK). These were predominantly confirmed to be hCB2 agonists, and upon comparison to a reference ligand (CP 55,940), four compounds exhibited signalling bias. Triazines 14 (UOSD017) and 15 were biased toward internalisation over cAMP and pERK, and 7 was biased away from pERK activation relative to cAMP and internalisation. Intriguingly, the triazine with an amino-PEG2-piperazinyl linker (13 [UOSD008]) was identified to be a mixed agonist/inverse agonist, exhibiting apparent neutral antagonism in the internalisation pathway, transient inverse agonism in the cAMP pathway and weak partial agonism in the pERK pathway. Both the cAMP and pERK signalling were pertussis toxin (PTX) sensitive, implying that 13 is acting as both a weak agonist and inverse agonist at CB2 via Gαi/o. Compound 10 (UOSD015) acted as a balanced high intrinsic efficacy agonist with the potential to produce greater hCB2-mediated efficacy than reference ligand CP 55,940. As 10 includes a Boc-protected PEG2 moiety it is also a promising candidate for further modification, for example with a secondary reporter or fluorophore. The highest affinity compound in this set of relatively polar hCB2 ligands was compound 16, which acted as a slightly partial balanced agonist in comparison with CP 55,940. The ligands characterised here may therefore exhibit unique functional properties in vivo and have the potential to be valuable in the future development of CB2-directed therapeutics.